(untitled) (Physical Education, Health and Social Sciences, 2026)
The paper has examined how muscular strength and body composition affect wrestling performance in young male wrestlers aged between 18-25 years. The 20 wrestlers took part in the research, and they were subjected to strength tests by 1RM: bench press, squat, and deadlift, and body composition; the skinfold calculus and bioelectrical impedance analysis (BIA). The wrestling performance was measured using the match simulation success, endurance and agility measures. The outcomes revealed that there was a positive relationship existing between muscular strength and wrestling performance (r = 0.62) whereby wrestlers with strong or high muscular strength recorded the best results in wrestling performance. Equally, the lean body mass had a positive relationship with wrestling performance (r = 0.55) which shows the significance of muscle mass in increasing the endurance, power and technical skills. In their turn, the percentage of body fat was found to interrelate negatively with the performance (r = -0.48), which indicates that the lower the body fat, the more agile and efficient one will be in wrestling. The muscular strength along with the lean body mass was found via multiple regression analysis to contribute to 55.3 percent of the variance in wrestling performance with muscular strength as the most notable predictor. The results of the mentioned studies demonstrate the importance of strength and muscle mass in the performance of wrestlers, and body fat percentage is secondary. This research recommends strengthening of the body and building of muscle mass among wrestlers in the management of fat in the body to enhance performance. These findings have practical implications on wrestling coaches and athletes in which specific training methods are relevant. Further studies might also involve studying other factors that affect performance at wrestling.